O Auto da Floripes no lugar das Neves: um contributo da imagem em movimento para a perceção do fenómeno cultural - Tavares, Pedro Mota (CEM – Cultura, Espaço & Memória, 2020)
The present work has as its object of study the representation of the play Auto da Floripes. According to the theme previously mentioned, our main objective is, in first place, to analyze the relationship between this play – from its origins until, approximately, the end of the 1950’s – with the place called Neves and the religious devotion of the local saint. We also intend to analyse the particular contribution of the homonymous film, made in 1959, to the development of a theme that, on principle, has belonged to the field of Social and Human Sciences. In this sense, we used the documentary collection from Cineclube do Porto in order to understand, in the end – and from the existing documentation on the film –, the relationship between the ethnographic context in order to understand of Neves and the representation of Auto da Floripes itself.